Meta-analysis of the intervention effects of taekwondo on metabolic syndrome indicators - Han, Zhengfa; Ju, Hanyu (Frontiers in Physiology, 2023)
Objective: To quantify the effect of Taekwond on the intervention of Metabolic Syndrome(MS) indicators, and attempt to explore the intervention scheme that is capable of producing an ideal; Methods: Combining with databases of Cnki.net, Wanfang, PubMed, Web of Science, Embase,KISS, RISS, DBPIA, the paper will retrieve relevant references in Chinese, English and Korean, adopt Review Manager 5.4 software, and evaluate the methodological quality of the included references according to the Cochrane evaluation manual, as well as apply Comprehensive Meta-Analysis 3.7 software for statistical analysis. Result: There are total 45 references and 1079 subjects involved.The results ofMeta-analysis show that the intervention of Taekwond plays a positive role for all indicators of MS (ES = -0.615, -0.672, -0.497, -0.785, -0.591, 0.435; P < 0.05). The results of subgroup analysis show that the intervention effect of Taekwond on female’s MS is superior than male,the intervention effect on the middle-aged’ and the elderly’ MS is better than that of other age groups, and the intervention effect on people’s MS with abnormal MS indicators is better than that of normal people. Meanwhile, there are optimal effects when the intervention period exceeds 12 weeks, and when the intervention frequency is 3 times aweek, as well as when the intervention time is 40-50 minutes each time. In addition, when combining the intervention types of Poomsae, kicks and Taekwondgymnastics, there are optimal effects. The larger exercise intensity, the better effects. Conclusion: Taekwond is capable of effectively improving MS, highlighting with the decreaseof BMI, SBP, DBP, FBG, TG and the increase of HDL-C. Taekwond realizes an optimal effect onthe middle-aged and the elderly female with abnormal MS indicators. To maximize the interventioneffect of Taekwond on MS, it is appreciated to take 40-50 minutes each time, three times a week,and take high-intensity Poomsae, kicks and Taekwond gymnastics as the exercise prescription, as well as follow over 12 weeks.